(untitled) (Journal of Human Sciences, 2023)
Ghat town and some of its neighbouring areas are exposed to occasional torrential rains, but they may be dangerous and destructive in rare cases, as happened in June 2019. The study aims to propose solutions to protect Ghat and its surroundings from flood hazards in the future. Remote sensing (RS) and geographic information systems (GIS) were used to achieve this goal. Therefore, a satellite image taken from the European satellite (Sentinel 2) was relied upon to determine the areas that were subject to floods, and the paths of the wadies that swept the region at the beginning of June 2019. The digital elevation model (SRTM1) was also relied upon to conduct morphometric analyses and extract drainage networks for the wadies affecting Ghat and the surrounding areas, in addition to determining the best suitable places for the establishment of the proposed facilities. The study discussed the possible alternatives to avoid flood hazards in the region, and recommended the construction of three dams on the three most important wadies that affect Ghat town and its surroundings, provided that the priority in implementation is consistent with the order of their inclusion in the study.